An unusual case of metallic foreign body in the left knee: a rare case report - B., Ezhil Rajan; S., Reshma (International Journal of Research in Orthopaedics, 2017)
Foreign bodies in the knee joint are uncommon, particulary those not related to surgical procedures. We present a rare case of an intraosseous metallic foreign body penetrating the lateral femoral condyle at left knee causing pain, which was removed with complete resolution of the symptoms due to walking – running injury in a child.